Impact of contemporary patterns of chemotherapy utilization on survival in patients with advanced cancer of the urinary tract: a Retrospective International Study of Invasive/Advanced Cancer of the Urothelium (RISC). (25th October 2017) - Bamias, A; Tzannis, K; Harshman, L C; Crabb, S J; Wong, Y -N; Kumar Pal, S; De Giorgi, U; Ladoire, S; Agarwal, N; Yu, E Y; Niegisch, G; Necchi, A; et al.
Abstract: Background: Cisplatin-based combination chemotherapy is the standard treatment of advanced urinary tract cancer (aUTC), but 50% of patients are ineligible for cisplatin according to recently published criteria. We used a multinational database to study patterns of chemotherapy utilization in patients with aUTC and determine their impact on survival. Patients and methods: This was a retrospective study of patients with: UTC (bladder, renal pelvis, ureter or urethra); advanced disease (stages T4b and/or N+ and/or M+); urothelial, squamous or adenocarcinoma histology. Primary objective was overall survival (OS). Eligibility-for-cisplatin was defined by Eastern Cooperative Oncology Group performance status ≤ 1, creatinine clearance ≥ 60 ml/min, no hearing loss, no neuropathy and no heart failure. Cox regression multivariate analyses were used to establish independent associations of cisplatin versus noncisplatin-based chemotherapy on OS. Results: About 1794 patients treated between 2000 and 2013 at 29 centers were analyzed. Median follow-up was 29.1 months. About 1333 patients (74%) received first-line chemotherapy: the use of first-line chemotherapy was associated with longer OS: [hazard ratio (HR): 1.91, 95% confidence interval (CI): 1.67–2.20]. Type of first-line chemotherapy received was: cisplatin-based 669 (50%), carboplatin-based 399 (30%) and other 265 (20%). Cisplatin use was an independent favorable prognostic factor (HR: 1.54, 95% CI: 1.35–1.77). This benefit was independent of baseline characteristics or comorbidities but was associated with eligibility-for-cisplatin: eligible patients treated with cisplatin lived longer than those who were not (HR: 1.74, 95% CI: 1.36–2.21), while such benefit was not observed among ineligible patients. About 26% of patients who did not receive cisplatin were eligible for this agent. Median OS of ineligible patients was poor irrespective of the chemotherapy used. Conclusions: The importance of applying published criteria of eligibility-for-cisplatin was confirmed in a multinational, real-world setting in aUTC. The reasons for deviations from these criteria set targets to improve adherence. Effective therapies for cisplatin-ineligible patients are needed.